2021
DOI: 10.3390/ijerph18189471
|View full text |Cite
|
Sign up to set email alerts
|

New Nurses’ Experience of Caring for COVID-19 Patients in South Korea

Abstract: The purpose of this study was to explore the experiences of new nurses who took care of COVID-19 patients. For this study, study subjects were conducted with a total of nine new nurses, and data were collected through individual in-depth interviews from September to November 2020. The data were analyzed using the phenomenological analysis method suggested by Colaizzi. New nurses’ experience of caring for COVID-19 patients consisted of three categories. The three categories are “The fear as a new nurse about in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 13 publications
4
9
0
2
Order By: Relevance
“…A recent study (20) correlated the motivation of nurses engaged in the COVID emergency to the sense of duty and their career choice, and it reported how the pandemic has strengthened professional value. Nurses felt called into question, it was their moment, a mission for them, and they responded with courage, sense of responsibility and great sense of freedom, a freedom that is the ability to choose the good (21).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study (20) correlated the motivation of nurses engaged in the COVID emergency to the sense of duty and their career choice, and it reported how the pandemic has strengthened professional value. Nurses felt called into question, it was their moment, a mission for them, and they responded with courage, sense of responsibility and great sense of freedom, a freedom that is the ability to choose the good (21).…”
Section: Discussionmentioning
confidence: 99%
“…There are also studies that have found that nurses’ COVID-19 fears are at a high level ( Arpacioglu et al, 2021 ; Baysal et al, 2022 ; Khattak et al, 2021 ). In qualitative studies by Cakici et al (2021) , Ji & Lee (2021) , and Simeone et al (2022) to show the experiences of nurses caring for COVID-19 patients, the themes of uncertainty and fear, anxiety and fear of being infected, fear felt toward infectious patients, and loneliness and fear. The quantitative and qualitative data in the literature are similar.…”
Section: Discussionmentioning
confidence: 99%
“…The variable of age affected the night care behavior of nurses in the pandemic. In the COVID-19 pandemic, newly graduating nurses experienced stress because of restricted communication, an increasing workload, anxiety and fear, and a deficiency in professional competence ( Ji & Lee, 2021 ). In the present study, clinical nurses with 17 or more years of experience had a more positive perception of night nursing care and nursing interventions than those with 1–5 years of experience.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate a lower nursing intention among nurses than among undergraduate nursing students. While their identity as professionals has been enhanced for all nurses providing COVID-19 patient care, the fear of infection and burnout from excessive workload as well as the experience of deterioration of their daily life and that of their family [ 7 , 8 , 9 , 13 ] seem to have negatively affected them and therefore resulted in reduced nursing intention. This is also supported by the low nursing intention toward COVID-19 patients among undergraduate nursing students with field experience in COVID-19 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the demand for more nurses to care for COVID-19 patients in clinical settings, the current status of field practice by undergraduate nursing students showed that up to 100% of field practice in 2020 was simulation practice [ 12 ], raising concerns about the practical ability of new nurses after graduation. According to a study on new nurses’ experience in COVID-19 patient care after joining the field during the COVID-19 pandemic, these nurses faced numerous challenges including lack of experience in handling infectious diseases in clinical fields, fear of transmitting the disease, and difficulty in working in protective gear before improving their nursing skills [ 13 ]. As new infectious diseases are emerging, investigating nurses’ educational needs for COVID-19 patient care can help create educational data for future EID cases.…”
Section: Introductionmentioning
confidence: 99%